Pengaruh Inovasi dan Orientasi Kewirausahaan terhadap Daya Saing UMKM Sektor Kuliner di Kecamatan Singaparna - Arif Amril Mubarok; Yudi Setia Rachmanda; Alfin Nur Arifah; Rina Madyasari (Pusat Riset dan Inovasi Nasional, 2026)
This research aims to examine the effect of innovation and entrepreneurial orientation on the competitive advantage of food sector MSMEs in Kecamatan Singaparna, Kabupaten Tasikmalaya. Culinary MSMEs serve a crucial function within the Indonesian economy, accounting substantially for job creation as well as gross domestic product; nevertheless, numerous encounter obstacles in sustaining competitive advantage because of limited innovativeness and weak entrepreneurial orientation, particularly in semi-urban areas like Singaparna. The present investigation adopted a quantitative correlational design through a survey approach. Research data were gathered by means of standardized survey questionnaires employing a five-point Likert scale involving eighty-seven MSME entrepreneurs chosen through purposive sampling together with the Slovin formula. The collected data underwent multiple linear regression analysis utilizing IBM SPSS. The findings indicate that innovation exhibits a positive and substantial impact on market competitiveness, and entrepreneurial orientation also has a positive and significant effect on competitiveness. Together, these two variables explain 72.5% of the variance in MSME competitiveness (Adjusted R² = 0.725). These findings support Schumpeter’s Theory of Economic Development and Lumpkin & Dess’s Entrepreneurial Orientation Theory. Practically, the study implies that culinary MSME actors need to enhance product, process, marketing, and organizational innovation while strengthening innovative, proactive, risk-taking, autonomous, and aggressive behaviors to improve competitiveness. This research fills a contextual gap by focusing on a semi-urban district where such studies remain limited.”.